Vertical graphene on rice-husk-derived SiC/C composite for highly selective photocatalytic CO2 reduction into CO. (April 2023) - Wu, Linyi; Li, Yipei; Zhou, Binghua; Liu, Jian; Cheng, Deliang; Guo, Shien; Xu, Keng; Yuan, Cailei; Wang, Mingxi; Hong Melvin, Gan Jet; Ortiz-Medina, Josue; Ali, Sajjad; et al.
Abstract: Coupling graphene-based materials with SiC nanostructures is one of the most feasible strategies to improve the photocatalytic CO2 reduction performance. Here, we synthesized the vertical graphene (VG) sheets on the SiC nanowires achieved from rice husks to form the VG@SiC/C composite, in which the VG sheets possess high surface area, excellent electrical conductivity, and chemical stability, and the SiC nanowires have a suitable bandgap for sunlight absorption. The resulting VG@SiC/C composite provides an enhanced photocatalytic reduction of CO2 to CO and CH4, yielding CO and CH4 evolution yields of 25.5 and 2.3 μmol g −1 h −1, respectively. The achieved CO yield is maximal so far among the SiC-based photocatalysts. The defective VG sheets promote the absorption of sunlight, enhance the CO2 adsorption and activation, increase the separation of photogenerated electron-hole pairs, improve the activity of photocatalyst, and thereby prompt the photocatalytic reduction of CO2 to CO with high yield and selectivity. Graphical abstract: We report that the vertical graphene sheets on the surface of rice-husk-derived SiC/C composite demonstrate the enhanced photocatalytic performance of CO2 reduction to CO with high yield and selectivity under simulated solar irradiation. Image 1 Highlights: The VG sheets could be achieved on the surface of rice-husk-derived SiC to form the VG@SiC/C. The superior photocatalytic CO2 performance was ascribed to the special structure and features of VG@SiC/C. The VG can prompt the sunlight absorption, the CO2 adsorption and activation, and the separation of electron-hole pairs. The VG@SiC/C showed photocatalytic reduction of CO2 with a CO yield of 25.5 μmol g −1 h −1 and a selectivity of 91.84%.